Exploring the predictive properties of the Hayes Ability Screening Index subtest background information in identifying individuals with MBID among in-patients with SUD - Braatveit, Kirsten J.; Assmus, Jörg; Hove, Oddbjørn (Frontiers in Psychiatry, 2022)
Introduction For individuals with substance use disorder (SUD), mild to borderline intellectual disability (MBID) goes undetected in treatment clinics. The Hayes Ability Screening Index (HASI) has been found to be a valid, time-saving screening instrument for MBID in SUD treatment. MBID can have significant implications for treatment planning and outcomes. Therefore, it is important to have methods for the early recognition of these comorbid conditions. Because of less sensitivity to recent or ongoing substance use, the HASI subtest background information may be particularly valuable as an early screening of MBID. The main aim was to investigate the convergent, predictive, and discriminant validity of the HASI subtest background information in identifying in-patients with SUD as MBID or non-MBID. Methods Eighty-four in-patients with SUD aged 19–64 participated in this multicentre study. MBID was diagnosed according to the ICD-10 using WAIS-IV, Vineland II, and self-reported childhood learning difficulties. Results The main finding was that, among the HASI subtests, background information was the strongest predictor. A HASI background information cut between 6 and 7 showed a sensitivity of 78% and a specificity of 72%. Conclusion The HASI subtest background information has acceptable convergent, predictive, and discriminant validity as a screening for MBID among in-patients in SUD treatment.